ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPOR BERAS DI INDONESIA - Mutiasari, Ni Komang; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Import activities that are carried out when a country is unable to provide for its needs occur because the country cannot produce efficiently. One of the commodities imported by Indonesia is rice. The objectives of this study are (1) to determine and analyze the effect of simultaneous consumption, rice production, population, and foreign exchange reserves on rice imports in Indonesia. (2) to determine and analyze the effect of consumption, rice production, population, and foreign exchange reserves, partially on rice imports in Indonesia. This study uses a quantitative approach method using secondary data, as many as 21 years and using a double log multiple linear analysis technique. The results showed that (1) consumption, rice production, population and foreign exchange reserves simultaneously had a significant effect on rice imports in Indonesia. (2) Consumption partially has a positive and insignificant effect on rice imports in Indonesia. Rice production partially has a negative and significant effect on rice imports in Indonesia. The total population partially has a positive and significant effect on rice imports in Indonesia. Partial foreign exchange reserves have a positive and significant effect on rice imports in Indonesia. Keywords: Consumption, Rice Production, Population, Foreign Exchange Reserves, Rice Imports in Indonesia.